NANOPARTICLE-MEDIATED DELIVERY OF CRYOPROTECTANTS FOR CRYOPRESERVATION - Stewart, Samantha (Cryo Letters, 2020)
Nanotechnology research has continued to garner interest and is investigated across a number of fields and industries, ranging from water treatment to clinical and biomedical applications. In biomedical research, for example, polymeric nanoparticles can be leveraged for controlled delivery of drugs and chemical compounds into cells. In cryobiological applications, polymeric nanoparticles can be utilized to deliver cryoprotectants (CPAs) and other protective agents, particularly those impermeable to the cell membrane, into cells to study their effects on cells during cooling down and warming back and at low temperatures. This perspective will discuss how polymeric nanoparticles have been used in cryobiology, with particular focus on how delivery systems have been specifically developed for low temperature applications and the potential for these systems going forward.